South Korea in the ASEAN‐centered regional network. Issue 1 (13th January 2023) - Teo, Sarah
Abstract: Relying on a networked perspective, this article argues that South Korea is an actor of relative importance in ASEAN's regional network, but it ultimately does not occupy a place that is more crucial than the association's other dialogue partners. In the context of ASEAN seeking to maintain its network power in an evolving Indo‐Pacific, South Korea has played a supportive role in ASEAN's pursuit of social access, brokerage links and minimizing its exit potential from the Indo‐Pacific network. South Korea's role, however, has been a comparably limited one rooted in specific functional areas and focused on certain ASEAN member states. While these efforts would certainly reinforce ASEAN's network power to some extent, the relatively thin network links between ASEAN and South Korea in other sectors suggest that there is little potential to expand cooperation beyond a functional and socioeconomic trajectory. 摘要: 本文基于网络化视角，认为韩国在东盟区域网络中是一个相对重要的行动者，但其最终没有占据比该联盟其他对话伙伴更重要的位置。在东盟寻求在不断发展的印太地区维持其网络力量这一情境下，韩国在东盟追求社会准入（social access）、经纪联系以及最大限度地减少其退出印太网络的可能性方面发挥了支持作用。不过，韩国的作用相对有限，植根于特定的功能性领域，并聚焦于某些东盟成员国。尽管这些举措肯定会在某种程度上加强东盟的网络力量，但东盟与韩国在其他部门中相对薄弱的网络联系表明，几乎没有潜力来将合作扩大到功能性轨道和社会经济轨道之外。 Resumen: Apoyándose en una perspectiva en red, este artículo argumenta que Corea del Sur es un actor de relativa importancia en la red regional de la ASEAN, pero en última instancia no ocupa un lugar más crucial que los otros socios de diálogo de la asociación. En el contexto de la ASEAN que busca mantener el poder de su red en un Indo‐Pacífico en evolución, Corea del Sur ha desempeñado un papel de apoyo en la búsqueda de ASEAN de acceso social, enlaces de corretaje y minimizando su potencial de salida de la red del Indo‐Pacífico. El papel de Corea del Sur, sin embargo, ha sido comparablemente limitado arraigado en áreas funcionales específicas y centrado en ciertos estados miembros de la ASEAN. Si bien estos esfuerzos ciertamente reforzarían el poder de la red de la ASEAN hasta cierto punto, los vínculos de red relativamente débiles entre la ASEAN y Corea del Sur en otros sectores sugieren que hay poco potencial para expandir la cooperación más allá de una trayectoria funcional y socioeconómica.